Interfacial solar vapor generation for desalination and brine treatment: Evaluating current strategies of solving scaling. (15th June 2021) - Zang, Linlin; Finnerty, Casey; Zheng, Sunxiang; Conway, Kelly; Sun, Liguo; Ma, Jun; Mi, Baoxia
Highlights: Zero-salt deposition of self-floating evaporator is realized via optimal structure. Physical cleaning can alleviate salt deposition of transporter-assisted evaporator. Ion rejection and ion exchange improve evaporation performance in salinity water. Hydrophobic modification prevents salt ions from passing through evaporation layer. Controlled salt deposition can harvest by-product salt while producing water. Abstract: Interfacial solar vapor generation, an efficient, sustainable, and low-cost method for producing clean water, has attracted great interest for application in solar desalination and wastewater treatment. Although recent studies indicated significant enhancement of overall performance by developing photothermal materials and constructing different dimensional systems, stable evaporation performance and long-term operation of the evaporator are hindered by severe scaling issues. In this critical review, we present the latest strategies in reducing salt accumulation on the evaporator for solar desalination and brine treatment. We first demonstrate the consequences of salt accumulation, and then discuss various self-cleaning methods based on bio-inspired concepts and other strategies such as physical cleaning, ion rejection and exchange, fast ion diffusion, and controlled crystallization, etc. Importantly, we discuss and address the rational design of the evaporator via establishing a relationship model between its porosity, thickness, and thermal conductivity. Lastly, we evaluate salt-resistance strategies, evaporation performance, and possibilities of real application in different evaporation systems with scaling-resistant abilities. Graphical abstract: Image, graphical abstract